Bioactivity and efficacy of essential oils extracted from Artemisia annua against Tribolium casteneum (Herbst. 1797) (Coleoptera: Tenebrionidae): An eco-friendly approach - Deb, Mamata; Kumar, Dolly (Ecotoxicology and environmental safety, 2020)
Tribolium casteneum is a major stored grains pest causing huge loss by secreting toxic quinones’ which make the grains unfit for human consumption. Increasing concern about the fast-growing resistance in T. casteneum against fumigants has evoked more intense research worldwide. Therefore, finding an eco-friendly alternative for the management of the pest is of great importance. In this study, the insecticidal activity of the essential oils (EOs) of Artemisia annua is evaluated. Chemical composition of the EOs eluted with methanol and petroleum ether was analysed through Gas chromatography-mass spectrometry (GC-MS). The result has reported a total of 13 & 16 compounds in the methanol and petroleum ether EOs respectively. In contact toxicity studies, adults were found more susceptible to the petroleum ether EOs (LD50 = 0.43 mg adultˉ1) than the methanolic EOs (LD50 = 1.87 mg adultˉ1). Petroleum ether EOs was also superior in fumigant assays against both the adults (0.81 mg L air−1) and larvae (0.65 mg L air−1). Moreover, the same was also recorded as a strong repellent. The bio-molecular studies conducted to gain an insight into the extent of metabolic disturbances inflicted in the treatment sets has shown a significant increase in Lipid peroxidase and decrease (p˂0.01) in protein, Acetylcholinesterase, Glutathione S Transferees, Reduced Glutathione level. This indicates the major signs of oxidative stress in the treatment sets. The Results ascertain the knowledge to develop natural insecticides from Artemisia annua using a potential solvent to be used in the future as an efficient management tool against T. casteneum. [Display omitted] •Petroleum ether EOs was more efficient than methanolic EOs in the repellency and acute toxicity assays.•Increased oxidative stress reported in the lethal sets confirms the toxicity of EOs.•Presence of Deoxyqinghaosu in the petroleum ether EOs in a high amount indicate the better insecticidal property of the oil.•Essential oils (EOs) of Artemisia annua hold efficient insecticidal properties against Tribolium casteneum.